Tinjauan Hukum Mengenai Tindak Pidana Gratifikasi Layanan Seksual Menurut Undang-Undang Nomor 20 Tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi - Afriani, Kinaria; Merita, Enni; Candra, Andi (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract Corruption techniques and strategies are very diverse, which is a hot topic of discussion is the criminal act of corruption regarding gratification in the form of sexual services, which appears in the term sexual gratification. This research method is a normative juridical approach. Sexual service to recipients is a criminal act of corruption regarding gratuities as meant in Law Number 20 of 2001 concerning amendments to laws. Number 31 of 1999 concerning the Eradication of Corruption Crimes in the elucidation of Article 12B paragraph (1) UUPTPK. This is in accordance with the original intent of the UUPTPK itself, even though the crime of sexual gratification is not explained explicitly in the UUPTPK. There is a need for stricter sanctions against the crime of sexual gratification because it also tarnishes the nation with immoral acts, meaning that there is also a need for social sanctions which are also formulated in Law Number 20 of 2001 concerning amendments to Law Number 31 of 1999 concerning Eradication Corruption Crime